New systematic and phylogenetic data about the early Barremian Iguanodon galvensis (Ornithopoda: Iguanodontoidea) from Spain. (19th May 2018) - Verdú, Francisco Javier; Royo-Torres, Rafael; Cobos, Alberto; Alcalá, Luis
Abstract: Iguanodon galvensis is the second valid species in the European and Barremian large-ornithopod genus Iguanodon . In the present work, the I. galvensis holotype and referred material from the lower Barremian of Spain are described and discussed in detail. As a result, emended diagnoses of Iguanodon, I. galvensis and I. bernissartensis are proposed; I. galvensis can now be identified by three autapomorphies in the dentary, ischium and femur as well as a unique combination of characters. Moreover, I. galvensis is compared with other European Early Cretaceous large styracosternans. Finally, a new phylogenetic hypothesis is proposed that resolves Iguanodon ( I. bernissartensis, I. galvensis ) with the Valanginian Barilium dawsoni into a monophyletic clade (Iguanodontoidea).